Stress-Coping Strategies in Healthy Individuals and Patients with Atopic Dermatitis – Literature Review - Olbryś, Julia; Cyran, Piotr (Journal of Education, Health and Sport, 2025)
A chronic disease often disrupts the achievement of developmental tasks in a person’s life. It can also lead to a major decrease in self-esteem and interrupt the formation of identity. Atopic dermatitis (AD) is a chronic inflammatory skin condition that significantly impacts the quality of life of affected individuals, both physically and psychologically. Stress is not only a common consequence of AD but also a potential exacerbating factor for its symptoms. This review explores the stress-coping strategies employed by individuals with AD and compares them with those used by healthy individuals. By analyzing relevant studies, the aim is to identify psychological and behavioral patterns associated with AD and propose recommendations for improving stress management in this population. The findings highlight the importance of integrating psychological interventions into dermatological care to address both the emotional and physical challenges of AD.